Tik Tok the New Alternative Media for Youngsters for Online Sharing of Talent: An Analytical Study - Patel, Kesav; Binjola, Himani (Journal of Advanced Research in Journalism & Mass Communication, 2020)
Tik Tok, the new wave of social media which has introduced a new sub culture for the present generation and has brought a revolution in the social media for youngsters. Tik Tok has become a new platform for portrayal of talent for youngsters adding new meaning to already existing social media platforms. It is the fastest growing social media which has fascinated and engrossed so many youngsters across the globe and is one of the fastest growing in India. Tik Tok is basically the new alternative version of online sharing, that allows its users its interface for preparing short videos and music pieces. Tik Tok is the new obsession among youngsters which is giving them a platform to express them innovatively and ingeniously. The present paper is based on case study of individuals who used Tik Tok to highlight their talent. How to cite this article: Patel K, Binjola H. Tik Tok the New Alternative Media for Youngsters for Online Sharing of Talent: An Analytical Study. J Adv Res Jrnl Mass Comm 2020; 7(1): 17-20. DOI: https://doi.org/10.24321/2395.3810.202005